Gestión administrativa y su incidencia en el desempeño laboral del Gad. Municipal del cantón Echeandía, Provincia de Bolívar - Ulloa Ulloa, Jennyfer Abigail (2019)
Administrative management functions related to the control of staff performance, not only focus on verifying tasks and verifying process compliance. Currently, these functions are increasingly redirected towards the incorporation of good strategies (coaching, management, etc.) to optimize the maximum performance of human talent and link it towards the fulfillment of the objectives and goals of organizations. This final report developed based on previous research carried out in the Municipal Decentralized Autonomous Government of the Canton Echeandía - Province of Bolívar. The main objective of the investigation was: To analyze the incidence of administrative management in the labor performance of public servants of the aforementioned municipality. In the investigation carried out to the Municipality of Echeandía, it is detected that the main problems that affect the performance of public servants are: lack of motivation, high level of absenteeism, lack of training, inadequate infrastructure of the establishment, adequate equipment of the facilities or offices. According to these specific problems, a training plan to improve the performance of human talent based on issues related to coaching and its importance in the implementation of its principles in the municipal institution was issued as a means of solution or proposa